Real-time imaging of DNA damage in yeast cells using ultra-short near-infrared pulsed laser irradiation. - Estrella Guarino; Gheorghe Cojoc; Alfonso García-Ulloa; Iva M Tolić; Stephen E Kearsey (PLoS ONE)
Analysis of accumulation of repair and checkpoint proteins at repair sites in yeast nuclei has conventionally used chemical agents, ionizing radiation or induction of endonucleases to inflict localized damage. In addition to these methods, similar studies in mammalian cells have used laser irradiation, which has the advantage that damage is inflicted at a specific nuclear region and at a precise time, and this allows accurate kinetic analysis of protein accumulation at DNA damage sites. We show here that it is feasible to use short pulses of near-infrared laser irradiation to inflict DNA damage in subnuclear regions of yeast nuclei by multiphoton absorption. In conjunction with use of fluorescently-tagged proteins, this allows quantitative analysis of protein accumulation at damage sites within seconds of damage induction. PCNA accumulated at damage sites rapidly, such that maximum accumulation was seen approximately 50 s after damage, then levels declined linearly over 200-1000 s after irradiation. RPA accumulated with slower kinetics such that hardly any accumulation was detected within 60 s of irradiation, and levels subsequently increased linearly over the next 900 s, after which levels were approximately constant (up to ca. 2700 s) at the damage site. This approach complements existing methodologies to allow analysis of key damage sensors and chromatin modification changes occurring within seconds of damage inception.